Uncertainties in socially responsible design: a consequentialist approach. (14th February 2020) - Haug, Anders; Busch, Jacob
In recent decades, a plethora of books and papers on socially responsible design has emerged. This literature, however, has not led to the implementation of the solutions needed to solve the environmental and social problems faced by the world today. The lack of initiation of more ambitious projects can to a large extent be explained by the uncertainties associated with the effects of these, as well as the desirability of such effects. More specifically, it can be difficult to get support for highly ambitious projects if there is uncertainty (e.g., in the form of disagreements) about their beneficial effects or the fairness of the distribution of sacrifices needed to implement these. To be able to choose a more ambitious path, we need to better understand the uncertainties associated with socially responsible designs and to reconsider the ethical assumptions guiding our choices. This issue is addressed by defining a framework for understanding uncertainties associated with such projects and by arguing for a consequentialist ethics to govern socially responsible design.